2014
DOI: 10.1038/ng.3169
|View full text |Cite
|
Sign up to set email alerts
|

7q11.23 dosage-dependent dysregulation in human pluripotent stem cells affects transcriptional programs in disease-relevant lineages

Abstract: Cell reprogramming promises to make characterization of the impact of human genetic variation on health and disease experimentally tractable by enabling the bridging of genotypes to phenotypes in developmentally relevant human cell lineages. Here we apply this paradigm to two disorders caused by symmetrical copy number variations of 7q11.23, which display a striking combination of shared and symmetrically opposite phenotypes--Williams-Beuren syndrome and 7q-microduplication syndrome. Through analysis of transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
107
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(130 citation statements)
references
References 70 publications
12
107
0
2
Order By: Relevance
“…Genome-wide mRNA profiling in differentiated hepatocyte-like Huh7.5.1 cells overexpressing miR-146a-5p was performed using a GeneChip Human Gene 1.0 ST array (Affymetrix TSA) at the IGBMC Microarray and Sequencing Platform (Illkirch, France). Briefly, biotinylated single-stranded cDNA targets were prepared as described previously (33). Following fragmentation and end labeling, hybridization of 2.07 g of cDNAs was performed using a GeneChip fluidics station 450 instrument (Affymetrix) for 16 h at 45°C.…”
Section: Methodsmentioning
confidence: 99%
“…Genome-wide mRNA profiling in differentiated hepatocyte-like Huh7.5.1 cells overexpressing miR-146a-5p was performed using a GeneChip Human Gene 1.0 ST array (Affymetrix TSA) at the IGBMC Microarray and Sequencing Platform (Illkirch, France). Briefly, biotinylated single-stranded cDNA targets were prepared as described previously (33). Following fragmentation and end labeling, hybridization of 2.07 g of cDNAs was performed using a GeneChip fluidics station 450 instrument (Affymetrix) for 16 h at 45°C.…”
Section: Methodsmentioning
confidence: 99%
“…74 A separate study also identified an interaction between TFII-I and DNMT3B in iPSCs. 61 Interestingly, both the PCDH cluster and DPP6 were shown to undergo DNMT3B-mediated methylation, 75,76 and so it is possible that gene dosage of GTF2I might be involved in the DM profiles we detected at these loci. TFII-I has also been shown to bind to the promoter region of EZH2, encoding a member of the polycomb repressive complex 2 (PRC2), in embryonic stem cells, 77 which is the same cell type in which we observed enrichment of EZH2 binding sites and regions containing H3K27me3-marked chromatin, a characteristic of transcriptional silencing by PRC2, within DM probes.…”
Section: Discussionmentioning
confidence: 90%
“…Although it is currently unknown how transcriptional dysregulation resulting from GTF2I deletion can lead to the hypersocial (gregarious) phenotype in WBS, a recent study using human induced pluripotent stem cells (iPSCs) found that in the pluripotent state, GTF2I was responsible for 10–20% of the transcriptional dysregulation in disease-relevant pathways in WBS and 7q-microduplication syndrome (38). Furthermore, another report focused on a pair of genetic syndromes caused by symmetrical copy number variations (CNVs) at 7q11.23 involving the loss and gain of a number of genes, WBS and Williams-Beuren region duplication syndrome (also known as Somerville–van der Aa syndrome), respectively (26, 39); the latter includes an autistic spectrum disorder (7dupASD) (26, 39). The study concluded that 7q11.23 dosage imbalance could disrupt transcriptional circuits in disease-relevant pathways starting from the pluripotent state (Adamo et al, 2015).…”
Section: Role Of Tfii-i In Williams-beuren Syndrome (Wbs) and Other Nmentioning
confidence: 99%